2008
DOI: 10.1242/jeb.009175
|View full text |Cite
|
Sign up to set email alerts
|

Sodium uptake in different life stages of crustaceans: the water fleaDaphnia magnaStrauss

Abstract: + /Cl-exchanger. Differential sensitivity of neonates and adults to iono-and osmoregulatory toxicants, such as metals, are discussed with respect to differences in whole-body Na + uptake kinetics, as well as in the mechanisms of Na + transport involved in the whole-body Na + uptake in the two life stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 69 publications
1
41
0
Order By: Relevance
“…Consequently, the biotic ligand stability constant for sodium potentially incorporates the protective influence of competition for binding, alongside the uptake assistance provided by environmental sodium. Following on from this, Bianchini and Wood [37] identified a typical Michaelis-Menton-type relationship between environmental Na and Na uptake in juvenile D. magna, and found that the Na uptake assistance is saturable. Consequently, where environmental Na concentrations exceed the organism's uptake ability, only the true competitive binding effect is likely to exist, for which a smaller biotic ligand binding constant is likely to be representative.…”
Section: Significance Of Model Parametersmentioning
confidence: 88%
See 1 more Smart Citation
“…Consequently, the biotic ligand stability constant for sodium potentially incorporates the protective influence of competition for binding, alongside the uptake assistance provided by environmental sodium. Following on from this, Bianchini and Wood [37] identified a typical Michaelis-Menton-type relationship between environmental Na and Na uptake in juvenile D. magna, and found that the Na uptake assistance is saturable. Consequently, where environmental Na concentrations exceed the organism's uptake ability, only the true competitive binding effect is likely to exist, for which a smaller biotic ligand binding constant is likely to be representative.…”
Section: Significance Of Model Parametersmentioning
confidence: 88%
“…This is plausible, because other studies have shown environmental sodium to assist sodium uptake in D. magna, and in juvenile D. magna in particular [37]. Consequently, the biotic ligand stability constant for sodium potentially incorporates the protective influence of competition for binding, alongside the uptake assistance provided by environmental sodium.…”
Section: Significance Of Model Parametersmentioning
confidence: 94%
“…Size-dependent sensitivity would result from the inhibiting effect of copper on sodium uptake, associated with a higher sodium turnover in smaller species (see Grosell et al, 2002). Within species, mechanisms of sodium uptake may differ between stages and lead to differential sensitivity to metals (e.g., Daphnia magna neonates vs adults; Bianchini and Wood, 2008). In the present case, as snails were conspecific and of the same stage, the explanation may be still different: larger size may simply reflects generally higher fitness, including for tolerance to metal stress.…”
Section: Evolutionary Patternsmentioning
confidence: 99%
“…They are, for example, susceptible to changes of water chemistry as their iono-and osmoregulation (e.g. Na + , Ca 2 + ) critically depends on pH and on the presence of metal toxicants (Bianchini and Wood, 2008;Clifford and McGeer, 2009), which could be relevant in phases of soda application. In addition, high concentrations of abioseston as observed in the form of iron flocs (see above) are especially unfavourable for non-selective filter feeders such as daphnids (Kirk, 1991).…”
Section: Discussionmentioning
confidence: 99%